Overview of Stunting Incidents in Toddlers in the Work Region Puskesmas Wera - Faturahmah, Erni; Najmah, Najmah (Sean Institute, 2023)
Indonesia is the third country with the highest prevalence in Southeast Asia. In Indonesia, the average prevalence of stunting in toddlers was 36.4% in 2005-2017. The long-term impact of malnutrition in toddlers is disruption of brain development, intelligence, physical growth disorders and metabolic disorders in the body. The aim of this research is to find out the picture of stunting incidents in the Wera health center working area. Type of quantitative descriptive research. The variable in the research is a single variable, namely a description of the incidence of stunting. The research location was carried out in the working area of the Wera Community Health Center, Bima Regency, NTB in 2023. The population and sample in this study were all toddlers who experienced stunting using a sampling technique , namely total sampling . The research instrument used was a checklist sheet. Next, it is analyzed using univariate analysis . The research results show that in 2021 there were 66 (30.4%) stunted toddlers, while in 2023 there was an increase of 76 (35.1)% stunted toddlers. The highest number of stunted toddlers is Ntoke village, namely 28 (36.9%) stunted toddlers. Comprehensive efforts and prevention need to be made so that the problem of stunting toddlers is resolved, and in-depth research needs to be carried out regarding what factors are the most important as a result of the increase in stunting cases.